Redefining beauty: The refined perception of plus-size women by Adithira Hanim - Augusta, Zefanya Brilyanti Citra Ayuning Mega; Sujoko, Anang; Riani, Yuyun Agus (Universitas Bunda Mulia, 2025)
This study explores the portrayal of body positivity on social media, focusing on the Instagram plus-size influencer Adithira Hanim (@tiraemon). Utilizing Roland Barthes’ semiotic analysis, this research examines how visual and textual elements construct new beauty narratives that challenge traditional beauty norms. The analysis focuses on five key aspects of Adithira Hanim’s content: (1)Text captions, which convey empowering messages of self-acceptance and confidence; (2)Messages within the content, emphasizing body positivity, breaking stereotypes, and redefining beauty beyond thinness; (3)Settings, which provide context and reinforce the intended meaning behind the content; (4)Objects featured in the content, such as fashion, poses, and symbolic elements that influence beauty perception; and (5)Mood in content delivery, which affects audience reception and engagement. The findings highlight three key themes: (1)Body positivity as a means of self-empowerment, where Adithira Hanim utilizes her platform to encourage self-love and challenge societal beauty expectations; (2)The redefinition of beauty standards beyond thinness, promoting inclusivity by showcasing diverse body types as equally valuable and beautiful; and (3) Social media as an inclusive space, where digital platforms serve as alternative discourses that empower plus-size individuals to embrace their identities with confidence. Through fashion, lifestyle, and personal storytelling, Adithira Hanim plays a pivotal role in reshaping societal perceptions of beauty, advocating for more diverse and inclusive representations. This study underscores the transformative potential of social media in fostering body positivity and promoting a broader acceptance of beauty diversity.